PENGENDALIAN PERSEDIAAN DENGAN METODE ABC DAN EOQ PADA APOTEK KAFI PERUMAHAN BUKTI KEMILING PERMAI BLOK U NO.15 KECAMATAN KEMILING PERMAI KOTA BANDAR LAMPUNG - HIKMAH NURLAELATUL AZIZAH; Ahmad Sidiq; Emy Khikmawati (Industrika : Jurnal Ilmiah Teknik Industri, 2023)
Drugs are essential, if there is a shortage of a drug at the pharmacy can cause a vacancy, then what should be controlled, how much should be ordered, and when should be reordered. The purpose of this study is how the steps in the drug control process are the determinants, including the number of drug sales and knowing the planning and control system of drug inventory. The method in this study is the ABC classification analysis method to find out which drugs are the priority control, and the Economic Order Quantity (EOQ) method to find out how many drugs must be ordered each time the order process. In the ABC method, there are 32 types of drugs that are prioritized to be controlled because the investment value is quite high from the total 170 kinds of drugs found in the Kafi pharmacy. Then the right calculation is needed to find out the optimal number of orders, namely the Economic Order Quantity (EOQ) method. By applying this method, it will be very helpful for the management of Kafi Pharmacy because using the EOQ method of Kafi Pharmacy can save the total cost of inventory by 30,642%. Keywords: ABC Analysis, Drugs control, Economic Order Quantity (EOQ)